Fragmentations, phantom limbs, re-memberings: Negotiating bodies, representation, and subjectivity in Caribbean British writing - Gerlsbeck, Silvia (Journal of Postcolonial Writing, 2021)
This article examines representations of corporeality in Caribbean British writing and focuses on two novels in particular: George Lamming’s The Emigrants (1954) and David Dabydeen’s The Intended (1991). After outlining relevant insights from the field of body studies and discourses of the body in Caribbean literature, it argues that the novels focus on the body to voice similar concerns about writing, representation, and knowledge. The novel aspect of this article lies in its rereading of the texts’ foregrounding of issues of corporeality. Where corporeal imagery in postcolonial literatures has mostly been conceived as a symptom of the racialization and feminization of the “other” body as a legacy of colonialism, this article shifts the focus towards seeing the novels’ employment of the body as a negotiation of discourses of representation and subjectivity. In probing and problematizing constructivist and materialist conceptions, they furthermore negotiate important shifts in approaching “matter” in literary theory.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Body; David Dabydeen; George Lamming; materiality; representation; subjectivity